A Critical Review of Indonesiaâs Agrarian Reform Policy - Slamet Widodo (Journal of Regional and City Planning, 2017)
Abstract. Inequality in the agrarian structure in Indonesia remains a serious problem. Agrarian reform efforts have been the spirit of Indonesia since the enactment of the Basic Regulations on Agrarian Principles Act (UUPA). However, agrarian reform policies are still far from perfect. Since the reformation, the issue of agrarian reform, also known as land reform, regained its discourse space. The National Agrarian Reform Program (NARP) initiated by the government has tried to provide a holistic approach by not only focusing on land reform in the form of asset reform but by touching on the aspect of access reform. This paper attempts to analyze NARP using two approaches, i.e., the Objective-Constraint-Instruments and Sustainable Livelihood Framework Approaches. Through these two analysis models, an improvement model for holistic and sustainable agrarian reform was formulated. NARP has already been at an ideal level that combines assets and access reforms. Reflecting on some of the failures and weaknesses of NARP implementation, cross-sectoral coordination among all stakeholders should be performed. The land redistributed to the poor should be regarded as capital, thus, access reform in other areas is required, such as capital, technical skills, facilities, and infrastructure, as well as marketing.Keywords. policy, agrarian reform, land reform, rural areas.Abstrak. Ketimpangan struktur agraria di Indonesia masih menjadi permasalahan serius. Upaya pembaruan agraria telah menjadi semangat bangsa Indonesia sejak Undang-Undang Pokok Agraria (UUPA) diundangkan. Namun demikian bentuk kebijakan pembaruan agraria dirasa masih jauh dari sempurna. Sejak reformasi bergulir, isu pembaruan agraria yang dikenal juga sebagai land reform atau agrarian reform, seolah mendapatkan ruang diskursusnya kembali. Program Pembaruan Agraria Nasional (PPAN) yang digulirkan pemerintah mencoba memberikan pendekatan yang holistik, tidak saja memandang pembaruan agraria berupa asset reform, namun menyentuh pula pada aspek access reform. Tulisan ini mencoba menganalisis PPAN dengan dua pendekatan, yaitu Objective-Constraint-Instruments Approach dan Sustainable Livelihood Framework. Melalui dua analisis ini, kemudian dirumuskan perbaikan model pembaruan agraria yang holistik dan berkelanjutan. PPAN pada dasarnya sudah berada pada tataran ideal yakni menggabungkan asset dan access reform. Berkaca pada beberapa kegagalan dan kelemahan implementasi PPAN, perlu dilakukan koordinasi lintas sektoral antar semua pemangku kepentingan. Tanah yang diredistribusikan kepada masyarakat miskin, harus dipandang sebagai modal sehingga diperlukan acess reform pada bidang lainnya, seperti permodalan, keterampilan teknis, sarana dan prasarana, serta pemasaran.Kata kunci. kebijakan, pembaruan agraria, land reform, agrarian reform, perdesaan.